No kidding, mermaids are a joke! : the story of the little mermaid, as told by the prince - Loewen, Nancy, 1964-; Tayal, Amit (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2014)
Introduces the concept of point of view through the prince's retelling of the classic fairy tale "The Little Mermaid"--
Keywords: Fairy tales; Humorous stories